Penyiaran Televisi dan Radio di Era Digital: Analisis Etika dan Kepatuhan Regulasi Berdasarkan Data KPI Pusat Tahun 2025-2026 - Kundori; Edi Giantoro; Yuni Wulandari (Yayasan Tri Edukasi Ilmiah, 2026)
This study aims to analyze the mapping of ethics and regulatory compliance among television and radio broadcasting institutions in Indonesia during the post-Analog Switch Off (ASO) digital multi-channel era. Amidst hyper-competition and the pressure of the attention economy, broadcasting companies often perform calculated risks that neglect the Pedoman Perilaku Penyiaran dan Standar Program Siaran (P3SPS). Utilizing a descriptive qualitative approach with a case study design, this research examines official administrative sanction documents and circular letters issued by the Indonesian Broadcasting Commission (KPI) Pusat from 2025 to the first quarter of 2026. The results reveal three major systemic typologies of violations: first, a failure in internal corporate gatekeeping, evidenced by the mass violation of cigarette advertising regulations across 9 major TV stations ; second, a degradation of journalistic ethics in afternoon news slots characterized by trauma commodification and sensationalism ; and third, the exploitation of adult-oriented borderline content disguised under teenage (R) age classifications. Concurrently, KPI Pusat continues to optimize its preventive functions through religious and cultural circular letters, which achieved a 100% compliance rate. The study concludes that while KPI Pusat operates optimally within its regulatory framework, broadcasting institutions must reinforce their automated internal screening systems and implement strict internal key performance indicator adjustments to mitigate ongoing operational and economic risks.